ANALISIS ION MERKURI (II) MENGGUNAKAN NANO PARTIKEL PERAK TERIMOBILISASI PADA KERTAS SARING - Nessi Meileza; M. Lutfi Firdaus; Elvinawati Elvinawati (University of Bengkulu, 2018)
The aims of this research is improve stability and sensitivity of silver nanoparticles (NPP) immobilizatied on filter paper. Silver nanoparticles synthesized by reducing the ascorbic acid using a chemical reduction method. Immobilization NPP on filter paper is done with the technique of immobilization (immunosystem) is the process of molecular bonding reagent in supporting materials, so physically bound NPP the surface of filter paper is composed of cellulose fibers. The results obtained for the stability of immobilization NPP on filter paper can be last up to stable 60-daywhile liquid NPP stability can only last for 30 days. To maintained the stability ofimmobilization on filter paper is saved in a closed box. For the determination of sensitivity of immobilization NPP in the filter paper test is performed against the mercury (II) ion with each different concentrations. The results obtained for sensitivity of immobilization NPP on the filter paper is analyzed in digital image can be detect mercury (II) ion until the concentration of ppb. The results of measurement Limit of Detection (LOD) or limit the smallest NPP can detect mercury (II) ion is under 0.863 ppb, while liquid NPP able to detect only concentration 1.448 ppb.. The results of this research NPP immobilization on filter paper can be an alternative to increasingstability and sensitivity of NPP compared with liquid NPP, and can be applied into the colourimetry indicator is inexpensive and practical to analysis of mercury (II) ion in the digital image.